2011
DOI: 10.1002/tax.601007
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic inference in Leucodon Schwägr. subg. Leucodon (Leucodontaceae, Bryophyta) in the North Atlantic region

Abstract: Systematic and biogeographic relationships of mainly European and North American taxa of the moss genus Leucodon subg. Leucodon are inferred by phylogenetic reconstructions and haplotype analyses, based on sequence data from three plastid regions and nrITS. The two Macaronesian endemic species L. canariensis and L. treleasei are clearly separated from each other and from L. sciuroides, which is widespread in Eurasia including Macaronesia. A well‐supported sister‐group relationship with the American species L. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 46 publications
0
18
0
1
Order By: Relevance
“…The latter, however, can often be solved by amplifying ITS1 and ITS2 separately, which has also been done in phylogenetic analyses of bryophytes (e.g. [34]). Until now, mostly ITS2 has been considered as plant DNA barcode marker [32], [35].…”
Section: Discussionmentioning
confidence: 99%
“…The latter, however, can often be solved by amplifying ITS1 and ITS2 separately, which has also been done in phylogenetic analyses of bryophytes (e.g. [34]). Until now, mostly ITS2 has been considered as plant DNA barcode marker [32], [35].…”
Section: Discussionmentioning
confidence: 99%
“…For the ITS1 and 2, the PCR program employed was 40 cycles of 30 s at 95uC, 30 s at 52uC, and 1 min 30 s at 72uC, with the primers '18SF' and '26SR' (Rydin et al, 2004;Stech, 1999). In a few cases, the internal primers '5.8SC' and '5.8SN' (Bartish et al, 2005) were employed to get the entire sequence.…”
Section: Molecular Methodsmentioning
confidence: 99%
“…2.0 or 3.1), and the sequencing products were cleaned using the DyeEx 96 Kit (Qiagen). The same primers as for the initial PCR were used, or sometimes 'ITS4-bryo' and 'ITS5-bryo' (Stech, 1999) were used for ITS. Sequencing products were resolved on an ABI3100 automated sequencer.…”
Section: Molecular Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has, however, also been suggested that the wide distributions of bryophytes hide significant cryptic species diversity (Mishler and Oliver 2009), and several studies have indeed provided evidence for relatively frequent cryptic speciation among bryophytes (Hedenäs 2009a;Heinrichs et al 2009). Also when cryptic speciation is absent, infraspecific variation with a clear phylogeographic component is common among bryophytes (Hedenäs 2009a;Heinrichs et al 2009;Laenen et al 2010;Stech et al 2011). This shows that the different genotypes are adapted to the local or regional conditions where they occur, there are significant barriers against unhindered spore dispersal between habitats that appear suitable to a species, or that the time has not been sufficient for the species to reach all potential locations.…”
Section: Introductionmentioning
confidence: 95%